Beden tamlığının ihlali ve ölüm hallerinde doğan maddi zararların hesaplanması ve tazminatın tayini - Gürbüz, Metin (My University, 2000)
Beden tamlığının ihlâlî ve Ölüm Hallerinde Doğan Maddi Zararların Hesaplanması ve Tazminatın Tayini isimle tezimiz iki bölüm halinde hazırlanmış olup, birinci bölümde; bedensel zararlar, ikinci bölümde maddi zararların hesaplanması ve maddi tazminat kavramı ve tayini üzerinde durulmuştur. İnsanın beden ve ruh sağlığı ve yine yaşam hakkının kutsallığına saldırı teşkil eden gerek sözleşmeye aykırı hareketten doğan gerekse haksız fiilden doğan zararların tam olarak tazmini hukuk sistemimizde her zaman tartışılan güncelliğini kaybetmemiş bir konudur. Zarar görenin gelecekteki gelirinin hangi oranda arttırılacağı ve hangi oranın gerçek reel artışı temsil ettiği istatistiki veriler yardımı ile ortaya konulmuştur. Geleceğe yönelik bir zararın tazmininde matematik ilkeler ön plana çıkmaktadır. Tazminatın sermaye olarak hüküm altına alınacağı hallerde, sermayeleştirme işleminin hangi yöntem ile yapılacağı, bu yöntemlerin farklı sonuçlara vermesi nedeniyle önem kazandığından, sermayeleştirme teknikleri üzerinde durulmuştur. Yine meydana gelen zararın tam olarak tazmin edilebilmesi için, zarara yol açan eylem nedeniyle, meydana gelen faydalardan hangilerinin indirilip indirilemeyeceği sorunları incelenmiştir. Maddi tazminat kavramı ve özellikle, destekten mahrum kalma ve destekten yoksan kalma tazminatı incelenmiştir. Tazmin borcunu doğuran sorumluluk çeşidine göre olaya uygulanacak zamanaşımı sürelerin hangileri olduğu üzerinde durulmuştur. Tazminat borcunu sona erdiren sebepler üzerinde durulmuştur. Our thesis is prepared in two parts; one of the part is named Infringement (corrupting) of the Body -complete and Calculating of the Corporal(material) harms that occur because of the Death and The Appointing of the Indemnification In the first period the harms that occur in the body and in the second period the Calculating of the Corporal(material) harms and the Appointing of the Indemnification are studied. The Indemnifying of the harms of the attack to the body-health and to the spiritual-health of the human-being and also to the holy-life of the human -being and the Indemnifying of all these harms which occur from an unjustice or an illegal action against the contract have always been very important and current. The rising-rate of the credit or income of the harmed-person in the future and the amount of the rate to be increased and the real increasing rate of the income are given according to the statistic data. In the indemnifying of the harms to be occured in the future the mathematical principles are to be performed and the methods of the capital-performing implementation has become very important since all these methods give different results in the positions where the indemnification is to be resoluted as the capital and thus the techniques of having capital have become very important. And also to indemnify the harm to be seen complately , the problems of deciding on the decreasing art and amount of the occured and performed profit or income has been examined because of the action which caused to the harm. The concept of the Corporal(material) indemnification and especially the lack of supporting indemnifying have been examined deeply. Also the law prescriptions which cause the indemnifying obligation of the period to be performed in such an event about this subject is examined mainly. The reasons which cause to end the obligation of the indemnification was Very imported and studied on them.
Keywords: İş Güvenliği-Türkiye; Sosyal Güvenlik-Türkiye